Comparative studies of pure cultures and a consortium of white-rot fungi to degrade a binary mixture of dyes by solid-state fermentation and performance at different scales. (November 2019) - Jiménez, Sara; Velásquez, Carolina; Mejía, Felipe; Arias, Mario; Hormaza, Angelina
Abstract: White-rot fungi have been widely used in pure culture and consortia for treating recalcitrant compounds, such as synthetic dyes, since they are able to cleave and mineralize lignin using ligninolytic enzymes. Moreover, solid-state fermentation stands out in the treatment of dyes due to its low environmental impact. In this study we evaluated the degradation of allura red and tartrazine adsorbed onto corncob by either pure cultures or binary consortia of Trametes versicolor and Pleurotus pulmonarius . We performed a comparative study in terms of culture conditions optimization, degradation, activity of ligninolytic enzymes kinetics, and cytotoxicity assessment to unravel the differences between using individual cultures or consortium of white-rot fungi. 94% of the dye mixture was degraded in pure cultures, but only 64.3% was broken-down by the consortium. Enzymatic activity and degradation kinetics showed that T. versicolor maximum laccase activity corresponded to the plateau phase of degradation whilst for P. pulmonarius and consortium no match between both profiles was found. Also, T. versicolor extracts were not cytotoxic to CHO–K1 cell line. The process was therefore magnified using T. versicolor in pure culture. The degradation efficiency was maintained in all the sizes, allowing an increase of 20 times the amount of treated dyes. Highlights: Pure cultures of WRF are more efficient than consortia in the degradation of dyes by SSF. T. versicolor is the most suitable system for bioremediation of synthetic dyes. The enzyme laccase is directly related to the degradation of the mixture of dyes. A scale-up by a factor of 20 was achieved without losing efficiency.